Securely leverage open-source software with Python AI toolkit for IBM z/OS - Bostian, Joe; Rivera, Evan (IBM Redbooks, 2023)
Open-source software (OSS) is widely available and serves as an essential component for enterprises in the artificial intelligence (AI) and machine learning (ML) industry. Specifically, the open-source programming language Python is one of the most versatile and popular programming languages that are used in the world at the time of writing. This situation is especially true in the data science community, where Python provides many libraries and tools that enable essential AI and ML functions, and where it is supported by a large community of developers that actively contribute to its development. Understanding and managing vulnerabilities within OSS can be complex because of the many components, dependencies, and contributors that are involved. Although the nature of OSS helps balance access to programming and technology, it also results in fast-paced changes to software, which emphasizes the importance of software currency to minimize security concerns. Enterprises understand the critical need to have access to and leverage reputable open-source projects with proper maintenance, updates, transparency, reliable support, and a sense of control to form a secure foundation for implementing AI solutions. Python AI Toolkit for IBM® z/OS® is a powerful set of tools and libraries that is used to establish a secure foundation for AI development and deployment on z/OS so that enterprises can leverage their existing infrastructure for these mission-critical applications. The OSS that is provided within Python AI Toolkit for IBM z/OS is scanned and vetted for security vulnerabilities so that users can make informed decisions when leveraging these Python packages. Packages can be installed and managed by using the Package Installer for Python (pip), which is a common Python package manager, enabling a familiar, flexible, and agile delivery experience while empowering developers to build AI solutions.